2005
DOI: 10.1007/s10840-005-0910-0
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Feasibility of Coronary Sinus Left Ventricular Leads Extraction: A Preliminary Report

Abstract: our study suggests that CS leads could be easily and safely removed without any complication, also when placed in a CS branch, at least for relatively young catheters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 7 publications
2
16
0
Order By: Relevance
“…Of the three cases that required ES assistance, only one was observed to have formed a fibrotic attachment to the CS. In contrast, De Martino et al 15 reported on a series of 12 patients with passive fixation CS leads implanted for a similar length of time (mean 13.9 ± 11.7; range, 3–46 months) with all cases achieving successful removal with direct traction alone. They identified scar formation in the superior vena cava and lead‐lead binding as adhesion sites.…”
Section: Discussionmentioning
confidence: 95%
“…Of the three cases that required ES assistance, only one was observed to have formed a fibrotic attachment to the CS. In contrast, De Martino et al 15 reported on a series of 12 patients with passive fixation CS leads implanted for a similar length of time (mean 13.9 ± 11.7; range, 3–46 months) with all cases achieving successful removal with direct traction alone. They identified scar formation in the superior vena cava and lead‐lead binding as adhesion sites.…”
Section: Discussionmentioning
confidence: 95%
“…The latter will also lead to an increasing requirement for coronary sinus lead extraction. Experience in removal of these leads is being published 16–19 . The CS leads that were part of CRT devices were all removed with gentle traction.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, 4 of the 13 patients had leads that were less than 6 months old [22]. De Martino et al [23] reported 12 CS consecutive successful lead extractions in which the leads were 13.9±11.7 months old (3 were <6 months old). In all cases, manual traction was all that was required for lead removal [23].…”
Section: Coronary Sinus Leadsmentioning
confidence: 99%
“…De Martino et al [23] reported 12 CS consecutive successful lead extractions in which the leads were 13.9±11.7 months old (3 were <6 months old). In all cases, manual traction was all that was required for lead removal [23]. Burke et al [24] reported on 10 cases of CS lead extraction, seven of which were implanted less than 6 months.…”
Section: Coronary Sinus Leadsmentioning
confidence: 99%